Question:
Solution:
a) Consider the following equation:
![(x+4)(x-2)=7](https://img.qammunity.org/2023/formulas/mathematics/college/suhu00j8xs2l6rb62ffqw797k6rt9vw8xr.png)
applying the distributive property, we get:
![x^2+2x-8\text{ =}7](https://img.qammunity.org/2023/formulas/mathematics/college/1ioxivoopihzhkme52dpozoqv43ir0kftx.png)
now, putting all terms on one side of the equation, we get:
![x^2+2x-8-7=0](https://img.qammunity.org/2023/formulas/mathematics/college/kbzpckzfhc62o9awq366293boyhokmfcep.png)
this is equivalent to:
![x^2+2x-15=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/gnogi97qgzysmowb9vh7j5n3ydwyb8util.png)
Factoring this expression, we get:
![(x-3)(x+5)=0](https://img.qammunity.org/2023/formulas/mathematics/college/kf6l6eaoux3228gj53knrqbdq6b1g1epq5.png)
according to the equation, we can conclude that the solutions for the given equation are:
![x\text{ = 3}](https://img.qammunity.org/2023/formulas/mathematics/college/j4616zc20u9qxejnb0ndks0i4tf4zadluk.png)
and
![x=\text{ }-5](https://img.qammunity.org/2023/formulas/mathematics/college/3gfqrpms48yszeur9seihlyo2g2p5q2907.png)
b) Consider the following equation:
![6x^2+9x-22\text{ =0}](https://img.qammunity.org/2023/formulas/mathematics/college/g1eazidm8xtj3oegkh4lozvkzg6fjnhak5.png)
applying the quadratic formula:
![\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/kaoalb540qnvy45obw509ttuwfskx00e99.png)
where
a = 6,
b = 9
and
c = -22,
we obtain that the solutions of the given equations are:
![x\text{ =}\frac{-9+\sqrt[]{609}}{12}=\text{ 1.3}0](https://img.qammunity.org/2023/formulas/mathematics/college/fejskn3hl2xwdg0e5s0wmtvm44qxxz2e06.png)
and
![x\text{ =}\frac{-9-\sqrt[]{609}}{12}=\text{ -2.8}0](https://img.qammunity.org/2023/formulas/mathematics/college/2cgssmddigt65eq9dow4my5vekb26fyx1u.png)